2014
DOI: 10.1007/s12012-014-9243-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Rhizomes of Acorus gramineus Against Isoproterenol-Induced Cardiac Damage in Pigs

Abstract: The present study was designed to evaluate the cardioprotective potential of water extract of rhizomes of Acorus gramineus (AGR) against isoproterenol (ISO)-induced myocardial infarction. Male pigs were orally administered with 250 or 500 mg/kg of AGR or with vehicle for 9 days, with concurrent subcutaneous injections of ISO on the 8th and 9th day. Administration of AGR significantly ameliorated ISO-induced cardiac dysfunctions as evidenced by the ventricular ST-segment interval and R-amplitude as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This demonstrates that the water extract of the rhizomes of A. gramineus has significant cardiac protection potential and may be used to treat and prevent myocardial infarction [138]. The aqueous-methanolic extract of A. calamus has a therapeutic effect on ischemic heart disease mainly through the endothelium-dependent hyperpolarizing factor, which can regulate the coronary vasodilation effect and promote an increase in coronary blood flow [139].…”
Section: Cardiac Protection Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…This demonstrates that the water extract of the rhizomes of A. gramineus has significant cardiac protection potential and may be used to treat and prevent myocardial infarction [138]. The aqueous-methanolic extract of A. calamus has a therapeutic effect on ischemic heart disease mainly through the endothelium-dependent hyperpolarizing factor, which can regulate the coronary vasodilation effect and promote an increase in coronary blood flow [139].…”
Section: Cardiac Protection Activitymentioning
confidence: 95%
“…The crude extract of A. calamus has the effect of dilating coronary vessels, which provides a basis for the treatment of ischemic heart disease [139]. The essential oil of A. calamus has the effect of anti-atrial fibrillation, atrial fibrillation, ventricular arrhythmia, etc.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…VOA also showed great potential in the treatment of myocardial infarction. Jong-Hoon Kim et al (2014) found that VOA significantly improved the ISO-induced cardiac dysfunction. In addition, taking VOA can significantly reduce the increase of cardiac injury markers such as cardiac troponin T, tumour necrosis factor, myeloperoxidase activity and cardiac marker enzyme and prevent the consumption of antioxidant parameters.…”
Section: Pharmacological Activities and Mechanisms Of Volatile Oil Of...mentioning
confidence: 99%
“…in male pigs possesses significant cardioprotective potential against isoproterenol-induced myocardial infarction as it significantly attenuated increased cardiac injury markers, such as cardiac troponin T, tumor necrosis factor (TNF)-α, and myeloperoxidase activity, and cardiac marker enzymes, and prevented the depletion of antioxidant parameters [11]. 4.…”
Section: The Administration Of Water Extract Of Rhizomes Of Acorus Grmentioning
confidence: 99%